A Giant Pseudoaneurysm of the Forearm as Unusual Complication of Bacterial Endocarditis - Michele Arcopinto; Teresa Russo; Antonio Ruvolo; Antonio Cittadini; Luigi Saccà; Raffaele Napoli (Case Reports in Vascular Medicine)
A 59-year-old man with fever was diagnosed with endocarditis due to Streptococcus bovis. Two weeks after antibiotic therapy was started, he presented with red and painful swelling of the forearm without any sign of systemic inflammation. A giant hematoma connected to the radial artery was detected with ultrasound. Surgical intervention with the removal of multiple, sterile clots from the hematoma was performed, and the multiple lacerations of the artery detected were corrected. This is the first case reporting rupture of the radial artery as a complication of infective endocarditis.